(untitled) (International journal of artificial intelligence, 2026)
This article examines the content and effectiveness of a national educational model developed on the basis of Japanese preschool pedagogical principles such as Kaizen, O-soji, Omoiyari, and Mimamoru. The study was conducted through an experimental approach at Preschool Educational Institution No. 22 in the Quyi Chirchiq district of the Tashkent region. The experimental group consisted of 30 children from one senior group, while preparatory groups were selected as the control group. The program aimed to develop independence, self-care skills, empathy, care, and teamwork competencies in preschool children through daily activities and outdoor practical sessions. The results of the experiment demonstrated a significant improvement in social behavior and responsibility among children in the experimental group.